Modelling the energy consumption of socialized residential low-rise buildings in Metro Manila - Chan, Maxine Y.
According to the Philippines Energy Efficiency and Conservation Action Plan of 2016-2020, the Philippine residential sector accounted for approximately 26% of overall energy consumption, with the socialized housing bracket making up roughly 26% of this. Given this, there is a subsequent need to implement energy efficiency measures to reduce power usage, energy costs, and greenhouse gas (GHG) emissions. By analyzing household power consumption, a baseline energy performance model of a representative standard socialized housing low-rise building (LRB) was developed. This served as a tool to compare various scenarios that implemented technical solutions and household occupancy behavior. From the baseline model, it was shown that the appliances that were used the most would be the televisions (5.76-25.20 kWh/month), lightbulbs (3.60-42.48 kWh/month), and electric fans (11.52-136.08 kWh/month) regardless of household typology, amounting to around 21%, 21% and 35% of the total electricity use, respectively. The overall energy consumption of the representative building was determined to have an energy usage intensity (EUI) of 28.57 kWh/sqm/year, considering 100 household units as well as the common facilities. In terms of a per household value, the average power usage amounted to 79.2 kWh/month. For the scenarios, it was recommended that LED lightbulbs would be used to reduce energy costs.